Sejarah Perkembangan Masyarakat Muslim Tionghoa di Dungkek Kabupaten Sumenep Abad XVIII - Zainul Farid (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2020)
Abstract: The purpose of this research is to find out the phenomenon of Chinese ethnic life in the Madurese community. The focus of this article includes: 1) To describe the social and cultural life of the Chinese in Dungkek; 2) To Describe the History of Chinese Muslims in Dungkek; 3) To Describe the Development of Chinese Muslims in Dungkek. This article uses the historical method which consists of four stages, including: 1) Heuristic method (source collection) collecting data from books, articles, papers, journals and interviews. 2) Method of Verification (Source Criticism, which consists of internal criticism and external criticism. 3) Method of Interpretation (interpretation) or looking back at the sources obtained. 4) Historiographical method (historical writing) or presentation and reporting of research results. The data collection method was carried out by means of literature studies, field studies or interviews and archival studies. This article uses a historical approach, and uses the theory of Continuity and Change (change and development). The results of this study include: 1) History and the beginning of the entry of the Chinese into Dungkek village and what remains are there in Dungkek village. 2) History of the entry of the Chinese into the Islamic religion so as to improve the quality of good relations with the indigenous people and the entry of arts and businesses produced by the Chinese community into Dungkek Village. 3) Chinese Islamic values in marriage, in language, in religion, as well as in terms of tolerance among members of the community. With these developments, the socio-cultural economy of Dungkek village has also increased. Starting from agriculture, fishing and sculpture. Keywords: Chinese, Madura, Islam, aculturation